The Influence of Halal Certification, Muslim Influencers, and Lifestyle on Purchase Decisions with Trust as an Intervening Variable Among Generation Z in Serang City - Karomah; Hadi Peristiwo; Syihabudin; Wazin; Syaeful Bahri (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The halal cosmetics industry in Indonesia has experienced rapid growth alongside the increasing awareness of Muslim consumers, particularly Generation Z, regarding the use of products that comply with Islamic principles. Digital technology, the presence of Muslim influencers, and lifestyle changes play important roles in shaping consumer behavior and purchase decisions. However, conceptual gaps still exist in understanding the mechanism through which these factors influence purchase decisions, with trust serving as an intervening variable. The study employed a quantitative research method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The data analysis included tests of Convergent Validity, Discriminant Validity, Composite Reliability, Model Fit, Path Coefficient, R-Square (R²), and Hypothesis Testing. The results of the study indicate that halal certification has a significant positive effect on purchase decisions, with a T-statistic value of 9.337 and a P-value of 0.001. Muslim influencers also have a significant effect, with a T-statistic of 7.306 and a P-value of 0.000. Lifestyle has a significant effect on purchase decisions, with a T-statistic of 4.350 and a P-value of 0.001. Furthermore, halal certification has a significant positive effect on trust, with a T-statistic of 22.128 and a P-value of 0.000. Muslim influencers significantly affect trust, with a T-statistic of 7.536 and a P-value of 0.000. Lifestyle also has a significant effect on trust, with a T-statistic of 3.205 and a P-value of 0.001. The R-Square value of 0.987 indicates that the independent variables are able to explain 98.7% of the variance in purchase decisions. Trust is also proven to mediate the relationships among the variables, with a T-statistic of 5.842 and a P-value of 0.000. Halal certification, Muslim influencers, and lifestyle have a positive and significant effect on halal cosmetic purchase decisions among Generation Z in Serang City. These three variables also have a positive and significant effect on consumer trust. Trust has been proven to have a positive and significant effect on purchase decisions. The better the perception of halal certification, the role of Muslim influencers, and the implementation of a halal lifestyle, the higher the level of trust and the purchase decisions for halal cosmetics among Generation Z.